Temporal left ventricular ejection fraction variations and outcomes in wide population of cardiovascular patients with and without heart failure - Szczerba, Radosław; Żelazna, Wiktoria; Sokołowski, Jakub; Wyroba, Natalia; Wydrych, Zuzanna; Wita, Michał; Cichoń, Małgorzata; Orszulak, Michał; Mizia-Stec, Katarzyna; Wita, Krystian; Wybraniec, Maciej T. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHeart failure (HF) with improved ejection fraction (HFimpEF) was shown to be related with improved outcome but increase of left ventricular ejection fraction (LVEF) in patients without HF is of less known clinical significance. The aim of the study was to evaluate long-term prognosis in patients with different cardiovascular disorders, with and without HF, depending on temporal variations of LVEF.MethodsThe study covered 31 920 patients (median age 71 years, 37.7% females) with different cardiovascular disorders and at least two measurements of LVEF separated by ≥1 month. Clinical parameters were acquired from database of Academic Repository of Clinical Cases of Medical University of Silesia. HFimpEF was defined by LVEF increase ≥10% in HF patients in relation to baseline value. The endpoints were all-cause mortality and Major Adverse Cardiac and Cerebrovascular Event (MACCE).ResultsThe median follow-up time was 51.5 months and LVEF was measured median 2 times. HF was diagnosed in 12 152 patients (38.1%), of which 2 843 (23.4%) experienced HFimpEF. MACCE occurrence was greater in HF than non-HF patients (12.78%/year vs. 6.07%/year, p < 0.001). In patients with HF, Kaplan–Meier survival curves showed significantly lower MACCE occurrence in HFimpEF and stable LVEF than in decreased LVEF (11.46%/year vs. 12.5%/year vs. 21.6%/year; log-rank p = 0.199 and p < 0.001) and HFimpEF constituted one of independent predictors of MACCE (HR = 0.84, 95% CI: 0.76–0.93). Conversely, in non-HF population patients with LVEF improvement had higher MACCE occurrence than patients with stable LVEF and lower than deteriorating LVEF (6.97%/year vs. 5.72%/year vs. 14.55%/year respectively; log-rank p = 0.001 and p < 0.001).ConclusionsTemporal increase of LVEF corresponds with improved survival in patients with HF but not among non-HF patients.